2016
DOI: 10.1016/j.afjem.2015.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Medical Records in low to middle income countries: The case of Khayelitsha Hospital, South Africa

Abstract: IntroductionElectronic Medical Records (EMRs) have shown benefit for clinical, organisational, and societal outcomes. In low-to-middle-income countries, the desire for EMRs will continue to rise as increasing trauma and infectious disease rates necessitate adequate record keeping for effective follow-up. 114 nations are currently working on national EMRs, with some using both a full EMR (Clinicom) and a paper-based system scanned to an online Enterprise Content Management (ECM) database.MethodsThe authors soug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 20 publications
0
31
0
Order By: Relevance
“…Limitations of paper-based charts are discussed in South African literature, and studies advocate for the use of electronic records, which may lead to more complete information becoming widely available on disorders including AMI. 13 …”
Section: Discussionmentioning
confidence: 99%
“…Limitations of paper-based charts are discussed in South African literature, and studies advocate for the use of electronic records, which may lead to more complete information becoming widely available on disorders including AMI. 13 …”
Section: Discussionmentioning
confidence: 99%
“…In most of the LMICs; the need for a trained workforce in health informatics is great [51]. There are instances where computer illiterate and low morale to use the system are affecting the implementation [36,52]. Some of the challenges include related to EHIS software, cost drivers, interoperability, connectivity in rural set up and data quality [40].…”
Section: Poor Application Of Proven Diffusion Techniquesmentioning
confidence: 99%
“…A study conducted in South Africa, demonstrated difficulties with implementing a dual EHIS as a result of clinicians' resistance to using the EHIS and feel more comfortable using paper based system [52]. In Iran, the negative staff attitudes of system developers and lack of acceptability are the main barriers to successful implementation of hospital-based EHIS [50].…”
Section: Staff Resistancementioning
confidence: 99%
“…Phenotypic results from CBtest are usually in the form of laboratory reports on hard copy printouts or laboratory information system databases of hospitals in middle-income countries, with some countries in this group transitioning to electronic medical records (EMR), including Malaysia [ 137 , 138 , 139 ]. While hard copy laboratory reports meet the need for result deployment to attending clinicians for patient diagnosis, the information chain stops at this point, and is rarely extracted for further use.…”
Section: Advantages Of 16sngs For Bacterial Pathogen Detectionmentioning
confidence: 99%